Figs 54–57 in Coccolithophorids in Polar Waters: Pappomonas spp. Revisited ... - Thomsen, Helge A.; Østergaard, Jette B. (Zenodo, 2014)
Figs 54–57. Balaniger balticus / Pappomonas virgulosa combination cells. TEM whole mounts from West Greenland. 54 – complete cell with flagella and a single haptonema; arrows point to areas of the periplast where B. balticus HOL elements occur; 55 – detail from Fig. 54 showing B. balticus HOL pyramids; 56 – detail from Fig. 57 showing a pointed variant of the B. balticus HOL pyramids; 57 – complete cell with the B. balticus HOL periplast elements pointed out. ... : Published as part of Thomsen, Helge A. & Østergaard, Jette B., 2014, Coccolithophorids in Polar Waters: Pappomonas spp. Revisited, pp. 235-256 in Acta Protozoologica 53 (3) on page 253, DOI: 10.4467/16890027AP.14.022.1997, http://zenodo.org/record/12638350 ...